A Case of Portal Vein Gas Which was Treated Conservatively and was Potentially Related to the Behcet's Disease - Sasaki, Takeshi; Dohke, Mitsuru; Kashimura, Nobuichi; Nakamura, Fumitaka; Matsunami, Takashi; Yano, Tomoyuki (Nippon Shokaki Geka Gakkai zasshi, 2005)
Recent advanced diagnostic imaging has increasingly detected portal venous gas in clinical practice, and the number of reports on this subject has increased. Portal venous gas has been considered to be indicative of poor prognosis and to have a mortality of 75%, although many case studies have reported successful treatment and survival. In addition, some reports have warned against immediate abdominal surgery without initial consideration of the reasons for portal venous gas. Here, we report a patient with portal venous gas whom we were able to treat conservatively. Three years after treatment, the patient was diagnosed with Behcet's disease, which was potentially related to the portal venous gas event.